Synthesis of a Potential Precursor (Northern Fragment) for the Cyclic Depsipeptides Vioprolides A and C - Reineke, Noé Osorio; Grab, Hanusch A.; Bach, Thorsten (Synthesis, 2024)
The synthesis of a potential northern fragment for the cyclic depsipeptides vioprolide A and vioprolide C is accomplished. The prepared compound is a pentapeptide and displays the non-canonical amino acid dehydrobutyrine (Dhb) at its C-terminal end. The central position is taken by another non-canonical amino acid, (2S,4R)-4-methylazetidine carboxylic acid (Maz). A route to enantiopure N-Boc-protected Maz (N-Boc-Maz) is developed from l-pyroglutamic acid, and this building block is taken into thiopeptide formation at its C-terminal end by successively coupling serine and threonine fragments. The C-terminal threonine is dehydrated to Dhb before attaching a d-Leu-Ala dipeptide to the N-terminal site of Maz. Several intermediates are directly telescoped into the next reaction step. Starting from N-Boc-Maz, the assembly of the pentapeptide is complete in eight steps with an overall yield of 16%.
Keywords: amino acids; azetidine; ring contraction; peptides; stereoselective synthesis